Burial traditions and ceremonies of Ustrushona residents - Tugalov Boburjon Bakhodir Ogli (Zien Journals, 2023)
In this article, an attempt was made to provide information about the burial traditions and rituals of the inhabitants of Ustrushona based on written archeological sources.
Keywords: Ustrushona; burial; ceremony